Embodied Temporality and Care: A Life History Study of Middle-Aged and Older Adults with Severe Diabetes - Hyang Soo Kim; Ye Sung Lee; Young Su Park (Korean Association of Health and Medical Sociology, 2026)
This study explores how socioeconomically marginalized people living with severe diabetes experience and make sense of their illness and lives, and how these experiences shape their self-understanding of illness, practices of care, and future orientation. To address this question, the life histories of four low-income adults in their fifties and sixties living with severe diabetes were analyzed. The findings are as follows. First, diabetes narratives unfold within multiple, intersecting temporalities, including clock time, biographical time, embodied temporality, and temporal orientations that connect the past, present, and future. Embodied temporality functions as an ontological condition through which the body, the self, and the organization of everyday life are constituted. Second, the ways in which participants understand and accept the chronicity of illness give rise to different practices of care and future orientations. While some participants narrate chronicity in terms of loss and deprivation, others accept their altered bodies and the chronic nature of illness, describing transformations in their values and orientations toward the future. For these participants, care is not the outcome of autonomous choice but an ongoing practice of adjusting everyday life in response to changing bodily conditions, unforeseen circumstances, and socioeconomic constraints. By foregrounding embodied temporality, this study demonstrates how the body, self, time, and life course are mutually constituted through lived experience. It argues that care for chronic illness should be understood not as a matter of individual self-management or personal choice, but as an ongoing process of negotiating bodily conditions and social circumstances in the pursuit of a good life. In doing so, the study contributes to expanding sociological debates on illness, temporality, and chronic illness care within the sociology of health and illness.